Vectorworks for entertainment design : using vectorworks to design and document scenery, lighting, rigging, and audio visual systems - Allen, Kevin Lee (Routledge, 2021)
"Vectorworks for Entertainment Design is the first book in the industry tailored for the entertainment professional. This second edition has been extensively revised and updated, covering the most current details of the Vectorworks software for scenery, lighting, sound, and rigging. With a focused look at the production process from ideation to development to documentation required for proper execution, the book encourages readers to better create their own processes and workflows through exercises that build on one another. This new edition introduces Braceworks, SubDivision modelling, and scripting using the Marionette tool, and covers new tools such as Video Camera, Deform Tool, Camera Match, Schematic Views, and Object Styles. Fully illustrated with step-by-step instructions, this volume contains inspirational and aspirational work from Broadway, Concerts, Regional Theatre, Dance, and Experiential Entertainment. Exploring both the technical how-to and the art of design, this book provides Theatre and Lighting Designers with the tools to learn about the application and use it professionally. Vectorworks for Entertainment Design also includes access to downloadable resources such as exercise files and images to accompany projects discussed within the book"--